The dB in the .db: Vocaloid Software as Posthuman Instrument. - Bell, Sarah A. (Popular Music & Society, 2016)
This article presents an analysis of the Vocaloid voice synthesis software in order to explore what kind of instrument the synthetic voice is emerging to be. Vocaloid software exemplifies a database paradigm of cultural production analogous to that from which instrumental music has always drawn, but representative of a perspective on the voice as an increasingly malleable instrument. Furthermore, Vocaloid music production challenges notions of voice as revealing something essential about the body, resulting in works that subvert traditional expectations of bodies based on vocal pitch, and timbre.